Download presentation

Presentation is loading. Please wait.

Published byTiana Lynes Modified over 2 years ago

1
3.3 Solving Multi-Step Equations

2
A multi-step equation requires more than two steps to solve. To solve a multi-step equation: you may have to simplify the equation first by combining like terms.

3
Solve. 8x + 6 + 3x – 2 = 37 Example: 11x + 4 = 37 Combine like terms. – 4 – 4 opposite and balance 11x = 33 x = 3 Since x is multiplied by 11, divide both sides by 11. 33 11 11x 11 = Now check your solution!

4
Solve. -9x - 4 + 4x – 2 = 44 Check It Out! Example -5x - 6 = 44 Combine like terms. +6 +6 Since 6 is subtracted from -5x, add 6 to both sides. -5x = 50 x = -10 Since x is multiplied by -5, divide both sides by -5. 50 -5 -5x -5 = Now check your solution!

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google